Sustainability of Small Merchants Through Digital Technologies - Madhava Priya, D.; Prashanth, J.; Indira, A. (Prabandhan: Indian Journal of Management, 2019)
In the last two years, there has been an attempt to move towards a cashless society and create a Digital India. The Government of India is encouraging use of a variety of payment systems post demonetization in November 2016. The focus of this paper was to understand the use of point-of-sale (POS) systems installed by merchants and service providers for receiving payments from customers for transactions involving sale of goods and services to the public. The primary focus of the paper was to understand the adaptability, affordability, and sustainability of the payments system as seen from the point of view of small merchants. The paper is based on a study conducted in 2017, aimed at understanding the different types of payment systems that are available to the small merchants. It also looked at the difficulties faced by them and their effect on their businesses. A total of 221 responses were collected in Chennai, capital city of Tamil Nadu in South India. The results showed that cash remained the most preferred mode for business. Cash was required for working capital, payment of employee remuneration, wages, and others. With regards to the use of payment systems like POS, more awareness needs to be created about the benefits in having non-cash transactions. It seemed that the merchants would be convinced if it could improve credit worthiness and eligibility to receive loans from banks.